2022
DOI: 10.1038/s41598-022-23852-z
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a prognostic model for lung adenocarcinoma based on endoplasmic reticulum stress-related genes

Abstract: Lung adenocarcinoma (LUAD) is one of the most universal types of cancer all over the world and its morbidity continues to rise year by year. Growing evidence has demonstrated that endoplasmic reticulum stress is highly activated in cancer cells and plays a key role in regulating the fate of cancer cells. However, the role and mechanism of endoplasmic reticulum stress in lung adenocarcinoma genesis and development remains unclear. In this research, we developed a prognostic model to predict the overall survival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…10 PPP1R3G, a member of the PPP1R3 family, is implicated in multiple cellular biological processes, such as cellular proliferation, migration, apoptosis, and necroptosis. 8,11,12 The Human Protein Atlas database confirmed the expression of PPP1R3G in the placenta at the gene and protein level. However, the role of PPP1R3G in PE has not yet been explored.…”
Section: Impact Statementmentioning
confidence: 90%
“…10 PPP1R3G, a member of the PPP1R3 family, is implicated in multiple cellular biological processes, such as cellular proliferation, migration, apoptosis, and necroptosis. 8,11,12 The Human Protein Atlas database confirmed the expression of PPP1R3G in the placenta at the gene and protein level. However, the role of PPP1R3G in PE has not yet been explored.…”
Section: Impact Statementmentioning
confidence: 90%
“…VCP (valosin-containing protein) is crucial for maintaining mitochondrial function, and in prostate cancer cells, it employs self-aggregation to inhibit mitochondrial activity, thereby evading cell death during nutrient deprivation and promoting malignancy [ 32 ]. In a cohort study, Tao et al demonstrated that NUPR1 serves as a protective factor in the survival prognosis of LUAD [ 33 ], while Li et al suggested NUPR1 to be a potential risk gene [ 34 ]. NUPR1, a nuclear protein, plays a critical role in redox reactions [ 35 ], and macrophages have been implicated as the most relevant immune cells associated with NUPR1 expression in bladder cancer [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, we developed a novel prognostic model consisting of seven ERS-related lncRNAs. Previous studies have also constructed ERS-related models in various tumors, such as lung adenocarcinoma, breast cancer, hepatocellular carcinoma, and ovarian cancer [37][38][39][40] . However, the prognostic potential of ERS-related lncRNAs in HNSCC remains largely unexplored.…”
Section: Discussionmentioning
confidence: 99%